Surgical stabilization using segmental fixation with Steinmann nail and surgical wire in a canine with vertebral thoracolumbar luxofracture - Chipayo G., Ysaac (2019)
It is described the clinical case of a canine patient attended 30 minutes after a car accident, with a luxofracture of the thoracic vertebra 12 and its surgical treatment by a technique of segmental fixation of the thoracic vertebrae 11, 12 13 and lumbar 1, using a Steinmann nail and surgical wires. The patient presented with paraplegia and little response to the deep pain stimulus, which, in less than 24 hours after the first evaluation was null. This demonstrated the rapid deterioration of the medullary functions detectable in the clinical examination; however, the rapid action and the diagnostic images allowed the execution of the surgical technique before 24 hours after the injury. The patient recovered his posture and the march three days after surgery, managing to walk seven days after the intervention. These results confirm the need for a timely neurological evaluation with diagnostic criteria in order to make the appropriate surgical decision quickly.